Audit Aset Tetap Pada PT. XYZ - Maharani Putri Rabbani; Rida Perwita Sari (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to analyze the calculation of fixed asset depreciation at PT XYZ and evaluate its compliance with applicable accounting standards (PSAK 16). The research method used is quantitative analysis with secondary data sources, including financial statements and fixed asset lists of PT XYZ for the 2023 period. The analysis procedures include data collection, materiality determination, implementation of fixed asset audit procedures, and evaluation of findings. The research results show significant differences between the company's depreciation calculations and accounting standards. PT XYZ calculated depreciation of all fixed assets starting from August 2019, regardless of the actual acquisition date, while PSAK 16 requires depreciation to begin when assets are ready for use. This results in potential material misstatements in the financial statements, with higher book values of fixed assets and lower depreciation expenses than should be. Discussion of findings resulted in several improvement suggestions, including adding usage date column to the fixed asset calculation table, adjusting depreciation calculations according to acquisition dates, and evaluating the impact of non-compliance on the overall financial statements. In conclusion, the implementation of these suggestions will improve the accuracy and reliability of PT XYZ's financial statements, as well as ensure compliance with applicable accounting standards.